Osteoarthritis year 2011 in review: genetics - Meulenbelt, I. (Osteoarthritis and cartilage, 2012)
In the last decades, many researchers aimed to identify causal genetic variants by means of candidate gene analyses, genome wide linkage and association studies to elucidate underlying mechanisms of osteoarthritis (OA). Although several consistent genetic variants were identified the successes are limited. This review has a focus on studies published until mid 2011 and on data presented at the Osteoarthritis Research Society International 2011 (OARSI) in San Diego and that aim to elucidate the primary molecular and cellular events commencing OA onset in humans by applying genetic study designs.